Uptake of mass drug administration programme for schistosomiasis control in Koome Islands, Central Uganda. - Doreen Tuhebwe; James Bagonza; Elizabeth Ekirapa Kiracho; Adoke Yeka; Alison M Elliott; Fred Nuwaha (PLoS ONE)
Introduction Schistosomiasis is one of the neglected tropical diseases targeted for elimination in Uganda through the Mass Drug Administration (MDA) programme. Praziquantel has been distributed using community resource persons in fixed sites and house-to-house visits; however the uptake is still below target coverage. In 2011/2012 MDA exercise, uptake stood at 50% yet WHO target coverage is 75% at community level. We assessed the uptake of MDA and the associated factors in Koome Islands, Central Uganda. Methods In March 2013, we conducted a mixed methods cross sectional study in 15 randomly selected villages. We interviewed a total of 615 respondents aged 18 years and above using semi structured questionnaires and five key informants were also purposively selected. Univariate and multivariate analysis was done. MDA uptake was defined as self reported swallowing of praziquantel during the last (2012) MDA campaign. We conducted key informant interviews with Ministry of Health, district health personnel and community health workers. Results Self reported uptake of praziquantel was 44.7% (275/615), 95% confidence interval (CI) 40.8-48.7%. Of the 275 community members who said they had swallowed praziquantel, 142 (51.6%) reported that they had developed side effects. Uptake of MDA was more likely if the respondent was knowledgeable about schistosomiasis transmission and prevention (adjusted odds ratio [AOR] 1.85, 95% CI 1.22-2.81) and reported to have received health education from the health personnel (AOR 5.95, 95% CI 3.67-9.65). Service delivery challenges such as drug shortages and community health worker attrition also influenced MDA in Koome Islands. Conclusions Uptake of MDA for schistosomiasis control in Koome was sub optimal. Lack of knowledge about schistosomiasis transmission and prevention, inadequate health education and drug shortages are some of the major factors associated with low uptake. These could be addressed through routine health education and systematic drug supply for the successful elimination of schistosomiasis on the islands.